Ultrasound assisted endovascular treatment of acute venous thromboses - Heckmann, Markus B.; Wangler, Susanne; Katus, Hugo; Erbel, Christian (Vasa, 2019)
Deep vein thromboses lead to post thrombotic syndrome in up to 50% of patients, which entails significant morbidity and socioeconomic costs. Endovascular treatment of iliofemoral deep vein thrombosis aims to reduce the development and the severity of post thrombotic syndrome. This case series of four cases demonstrates that acute and chronic thrombotic stenoses or occlusions can be safely managed by ultrasound guided endovascular treatment minimizing the number of interventions, bleeding risk and radiation exposure.